Systematic review and meta-analysis of cell therapy for COVID-19: global clinical trial landscape, published safety/efficacy outcomes, cell product manufacturing and clinical delivery - Couto, Pedro S.; Al-Arawe, Nada; Filgueiras, Igor S.; Fonseca, Dennyson L. M.; Hinterseher, Irene; Catar, Rusan A.; Chinnadurai, Raghavan; Bersenev, Alexey; Cabral-Marques, Otávio; Moll, Guido; Verter, Frances (Frontiers in Immunology, 2023)
During the pandemic of severe respiratory distress syndrome coronavirus 2 (SARS-CoV2), many novel therapeutic modalities to treat Coronavirus 2019 induced disease (COVID-19) were explored. This study summarizes 195 clinical trials of advanced cell therapies targeting COVID-19 that were registered over the two years between January 2020 to December 2021. In addition, this work also analyzed the cell manufacturing and clinical delivery experience of 26 trials that published their outcomes by July 2022. Our demographic analysis found the highest number of cell therapy trials for COVID-19 was in United States, China, and Iran (N=53, 43, and 19, respectively), with the highest number per capita in Israel, Spain, Iran, Australia, and Sweden (N=0.641, 0.232, 0,223, 0.194, and 0.192 trials per million inhabitants). The leading cell types were multipotent mesenchymal stromal / stem cells (MSCs), natural killer (NK) cells, and mononuclear cells (MNCs), accounting for 72%, 9%, and 6% of the studies, respectively. There were 24 published clinical trials that reported on infusions of MSCs. A pooled analysis of these MSC studies found that MSCs provide a relative risk reduction for all-cause COVID-19 mortality of RR=0.63 (95% CI 0.46 to 0.85). This result corroborates previously published smaller meta-analyses, which suggested that MSC therapy demonstrated a clinical benefit for COVID-19 patients. The sources of the MSCs used in these studies and their manufacturing and clinical delivery methods were remarkably heterogeneous, with some predominance of perinatal tissue-derived products. Our results highlight the important role that cell therapy products may play as an adjunct therapy in the management of COVID-19 and its related complications, as well as the importance of controlling key manufacturing parameters to ensure comparability between studies. Thus, we support ongoing calls for a global registry of clinical studies with MSC products that could better link cell product manufacturing and delivery methods to clinical outcomes. Although advanced cell therapies may provide an important adjunct treatment for patients affected by COVID-19 in the near future, preventing pathology through vaccination still remains the best protection to date.